2000
DOI: 10.1046/j.1460-9568.2000.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 modulates neuronal threshold of vulnerability to ischaemic damage

Abstract: Interleukin-10 (IL-10) is a powerful suppressor of cellular immune responses, with a postulated role in brain inflammation. First, we have evaluated the role of this cytokine in ischaemic brain damage using IL-10 knockout (IL-10-/-) mice. The middle cerebral artery (MCA) was occluded in either IL-10-/- or wild-type animals of corresponding strain (C57Bl/6) and age. Infarct volume was assessed 24 h later in serial brain sections. Brain infarct produced by MCA occlusion was 30% larger in the IL-10-/- than in wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(129 citation statements)
references
References 36 publications
2
120
0
3
Order By: Relevance
“…Although the mechanisms underlying the ability of the brain to control inflammation are poorly understood, it has been reported that microglia in culture expressed IL-10 following exposure to LPS (Williams et al, 1996;Seo et al, 2004), and that IL-10 could exert immunosuppressive properties by downregulating the expression of pro-inflammatory cytokines such as TNF-α and IL-12 by microglia (Aloisi et al, 1997(Aloisi et al, , 1999b. Further, several studies have demonstrated neuroprotective effects of IL-10 against glutamate-mediated cerebellar granule cell death, hypoxic-ischemic neuronal cell death, and traumatic brain injury (Knoblach and Faden, 1998;Dietrich et al, 1999;Grilli et al, 2000;Bachis et al, 2001). These data strengthen the notion that the anti-inflammatory phox , p47 phox , and Rac 1 subunit from the cytosol to the plasma membrane; this translocation was sustained by IL-10NA.…”
Section: Discussionsupporting
confidence: 72%
“…Although the mechanisms underlying the ability of the brain to control inflammation are poorly understood, it has been reported that microglia in culture expressed IL-10 following exposure to LPS (Williams et al, 1996;Seo et al, 2004), and that IL-10 could exert immunosuppressive properties by downregulating the expression of pro-inflammatory cytokines such as TNF-α and IL-12 by microglia (Aloisi et al, 1997(Aloisi et al, , 1999b. Further, several studies have demonstrated neuroprotective effects of IL-10 against glutamate-mediated cerebellar granule cell death, hypoxic-ischemic neuronal cell death, and traumatic brain injury (Knoblach and Faden, 1998;Dietrich et al, 1999;Grilli et al, 2000;Bachis et al, 2001). These data strengthen the notion that the anti-inflammatory phox , p47 phox , and Rac 1 subunit from the cytosol to the plasma membrane; this translocation was sustained by IL-10NA.…”
Section: Discussionsupporting
confidence: 72%
“…IL-10, an anti-inflammatory cytokine, has a well-established role in neuroprotection (42)(43)(44)(45). In addition to acting on glia and endothelium to reduce inflammatory responses following ischemic brain damage, it directly protects cortical neurons by activating the PI3K/AKT pathway via IL-10 receptors on neurons (45).…”
Section: Resultsmentioning
confidence: 99%
“…42 Other experiments have shown that the infusion of a low dose of IL-1 receptor antagonist causes a 71% reduction in the volume of infarction induced by NMDA-receptor activation, 43 whereas the administration of IL-10, which has been related to neuroprotective actions, results in a reduction in glutamate-induced neuronal death. 44 One of the major questions in our study is whether increased inflammatory molecules in blood are the expression of brain ischemia or originate as a result of the acute-phase reaction or systemic causes. Several facts support the idea that plasma levels of IL-6, TNF-␣, and ICAM-1 within the first 24 hours of acute stroke reflect the total release of these molecules in the ischemic brain tissue.…”
Section: Discussionmentioning
confidence: 96%